An investigation into contact pressure distribution in bolted joints. (December 2014) - Stephen, JT; Marshall, MB; Lewis, R
Bolted joints are widely used in modern engineering structures and machine designs due to their low cost and reliability when correctly selected. Their integrity depends on quantitative representation of the contact pressure distribution at the interface during design. Because of the difficulty in reaching and assessing clamped interfaces with traditional experimental methods, presently bolted joint design and evaluation is based on theoretical analysis, with assumptions to quantify pressure distribution at the clamped interface, which may not represent their true operating conditions. The present work utilises a non-intrusive ultrasonic technique to investigate and quantify the pressure distribution in bolted joints. The effect of variation in plate thickness on the contact pressure distribution at bolted interfaces under varying axial loads is investigated. While it was observed that the contact pressure at the interface increases as the applied load increases, the distance from the edge of the bolt hole at which the distribution becomes stable is independent of the applied load on the bolted joint. However, the contact pressure distribution was observed to vary with the plate thickness. Although the variation in the peak value of the average contact pressure distribution in bolted joints does not depend on the plate thickness, the distance from the edge of bolt hole at which the value of the distribution becomes stable increases as the plate thickness is increased. It was also observed that the edge of the bolt head affected the position of the peak value of the contact pressure distribution at the interface, though its effect was dependent on plate thickness. Furthermore, a model based on a Weibull distribution has been proposed to fit the experimental data and a good correlation was observed.